2016
DOI: 10.1039/c6ta00052e
|View full text |Cite
|
Sign up to set email alerts
|

Robust nano-architectured composite thin films for a low-temperature solid oxide fuel cell cathode

Abstract: Nano-precipitates of Sm-doped CeO2 were uniformly coated onto porous Pt thin films via cathodic electrochemical deposition. Deposition of only 5 min created an oxide coating that increased the values of the electrode conductance by more than two orders of magnitude and provided outstanding thermal stability even at 600 °C for more than 100 h compared to the bare Pt electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…The detailed derivation process of out-diffusion solution from finite source is described in Supplementary Equations 1 – 3 . It should be noted that the obtained diffusion coefficient is ten orders of magnitude faster than that of a similar transition metal reported in ceria bulk lattice (e.g., Fe in Gd 0.1 Ce 0.9 O 1.95 38 ) when extrapolated to the same temperature (700 °C), and thus one can readily see the effectiveness of the grain boundaries for the migration of dopant cations. Lastly, the total amount of particles produced can be freely controlled by changing the supply of the metal source.…”
Section: Resultsmentioning
confidence: 58%
“…The detailed derivation process of out-diffusion solution from finite source is described in Supplementary Equations 1 – 3 . It should be noted that the obtained diffusion coefficient is ten orders of magnitude faster than that of a similar transition metal reported in ceria bulk lattice (e.g., Fe in Gd 0.1 Ce 0.9 O 1.95 38 ) when extrapolated to the same temperature (700 °C), and thus one can readily see the effectiveness of the grain boundaries for the migration of dopant cations. Lastly, the total amount of particles produced can be freely controlled by changing the supply of the metal source.…”
Section: Resultsmentioning
confidence: 58%
“…The CELD method developed for deposition on Pt electrodes [ 66 ] was further extended by the authors to forming low-temperature Ag-based composite cathodes [ 71 ]. Cathodic electrodeposition of Pr 0.2 Ce 0.8 O 2−δ (PCO) film onto the surface of 400 nm-thick nanoporous Ag electrodes, formed on a single-crystal 8YSZ substrate by magnetron sputtering, was performed using a traditional three-electrode system with a standard calomel electrode for a reference electrode, a carbon rod as a counter electrode and a tailor-made aluminum clip connected with Ag electrode, which served as a working electrode.…”
Section: Electrodeposition Technology For the Fabrication Of Sofc Air Electrodes With Increased Performancementioning
confidence: 99%
“…The PCO film covered the Ag columns with flake-like particles. In the top-view image of the Ag–PCO film, micrometer-scale cracks were observed, as in the case of the Pt–SDC electrode [ 66 ]. It was shown that only 45 s of the CELD process resulted in 33-fold improved activity of the electrode (121.5 and 3.7 Ω cm 2 at 450 °C).…”
Section: Electrodeposition Technology For the Fabrication Of Sofc Air Electrodes With Increased Performancementioning
confidence: 99%
“…Rare‐earth‐doped CeO 2 (ceria) has an excellent oxygen storage/supply capacity and sufficient oxygen ion/proton transport capabilities and is therefore widely used as a catalyst and an electrolyte in applications such as three‐way catalysts, hydrocarbon reformers, and solid oxide fuel cells (SOFCs). [ 1–10 ] In such devices, ceria is typically in close contact with other metallic components, including transition metals. Thus, metallic cations can penetrate into and/or react with ceria, especially when operating at high temperatures for long periods of time, eventually affecting the performance of the devices.…”
Section: Introductionmentioning
confidence: 99%